Temporal dominance of sensations of peanuts and peanut products in relation to Hutchings and Lillford’s “breakdown path" - Rosenthal, Andrew J.; Share, Carmen (Elsevier, 2014)
Hutchings and Lillford’s (Journal of Texture Studies, 19, 103-115, 1988) proposed a “breakdown path” whereby particle size reduction occurs through mastication in conjunction with the secretion of saliva to form a swallowable bolus. The swallowing trajectory of whole peanuts, peanut meal and peanut paste were studied with the temporal dominance of sensations technique. The sensations for whole peanuts progressed from hard, to crunchy, to chewy, to soft and ended compacted on teeth. Predictably peanut meal missed out the first two sensations, progressing from chewy, to soft and ending compacted on teeth. However peanut paste, which starts as a soft suspension with relatively little structure appears to thicken and stick to the palate during oral processing. We propose that the “hard to swallow” sensation elicited by peanut paste may be due to water absorption from the saliva as they mix in the mouth.